2003
DOI: 10.1016/s1044-0305(03)00144-2
|View full text |Cite
|
Sign up to set email alerts
|

Identification of 2D-gel proteins: A comparison of MALDI/TOF peptide mass mapping to μ LC-ESI tandem mass spectrometry

Abstract: A comparative analysis of protein identification for a total of 162 protein spots separated by two-dimensional gel electrophoresis from two fully sequenced archaea, Methanococcus jannaschii and Pyrococcus furiosus, using MALDI-TOF peptide mass mapping (PMM) and LC-MS/MS is presented. 100% of the gel spots analyzed were successfully matched to the predicted proteins in the two corresponding open reading frame databases by LC-MS/MS while 97% of them were identified by MALDI-TOF PMM. The high success rate from th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
96
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 124 publications
(101 citation statements)
references
References 51 publications
5
96
0
Order By: Relevance
“…This quantitative approach is based on the assumptions that the protein spots can be well resolved and that the changes in the normalized spot image intensity can be correlated with the expression level of particular proteins. However, as reported previously [16] and described here, multiple proteins are commonly identified from apparently single, well-resolved gel spots. Lim et al [16] reported that up to 60% of 2-D gel spots analyzed by LC-MS/MS contained multiple proteins per spot.…”
Section: Resultssupporting
confidence: 80%
See 2 more Smart Citations
“…This quantitative approach is based on the assumptions that the protein spots can be well resolved and that the changes in the normalized spot image intensity can be correlated with the expression level of particular proteins. However, as reported previously [16] and described here, multiple proteins are commonly identified from apparently single, well-resolved gel spots. Lim et al [16] reported that up to 60% of 2-D gel spots analyzed by LC-MS/MS contained multiple proteins per spot.…”
Section: Resultssupporting
confidence: 80%
“…However, as reported previously [16] and described here, multiple proteins are commonly identified from apparently single, well-resolved gel spots. Lim et al [16] reported that up to 60% of 2-D gel spots analyzed by LC-MS/MS contained multiple proteins per spot. Even with a relatively narrower pH range of 4-7 for IEF, more than 20% of the analyzed spots have been found to contain multiple proteins [32].…”
Section: Resultssupporting
confidence: 80%
See 1 more Smart Citation
“…It provides high sensitivity and reliability, and allows to reproducibly and to effectively match data to the predicted proteins (Lim et al 2003). The possibility of using LC-MS could be alternative to obtained better results.…”
Section: Comparison Of Maldi-tof With Other Methodsmentioning
confidence: 99%
“…The second approach is to modify the commercially available ZipTips from Millipore with a conductive electrode so they can be used directly on the Nanomate high-throughput platform. Much like the Poros resins, ZipTips have shown their utility for desalting and concentrating peptide, as well as protein samples [10,14,15]. The final approach is to modify the Nanomate itself such that a solvent gradient can be delivered from a liquid chromatography system through the Nanomate and across a disposable, either self-packed or commercial, chromatographic pipette tip.…”
mentioning
confidence: 99%